مراقبة حرائق الغابات في محمية النبي متى (محافظة طرطوس) باستخدام تقنيات الاستشعار عن بعد ونظم المعلومات الجغرافية (Latakia University Journal -Biological Sciences Series, 2012)
تتضمن هذه الدراسة تحليلا شاملا للعوامل المناخية والنباتية والطبوغرافية لمحمية النبي متى (منطقة الدريكيش- محافظة طرطوس – سوريا) كونها أهم العوامل المؤثرة في حرائق الغابات، حيث تم جمع البيانات المرافقة لكل حريق وتحليلها باستخدام البرامج الاحصائية (SPSS) و (EXCEL) ودراسة الارتباط المتعدد بين هذه العوامل وبين ظاهرة تكرار الحريق في منطقة معينة (خطر حدوث الحريق).تم بعد ذلك معالجة هذه البيانات ونتائج التحليل والارتباط المتعدد ضمن برنامج نظام المعلومات الجغرافية (GIS) للحصول على الخريطة الممثلة لمناطق خطر حدوث الحريق، وتمت الاستعانة بالخرائط الطبوغرافية بمقياس (1:50000), والصور الفضائية بمقياس (1:25000)، حيث صممت الخرائط اللازمة للدراسة (خريطة الانحدار – خريطة المعرض -  خريطة التغطية النباتية – خريطة البنية التحتية - خريطة مناطق خطر الحريق)، وتم اقتراح أماكن أبراج المراقبة ومراكز التدخل السريع ضمن المناطق ذات درجة الخطورة العالية لحدوث الحرائق. تعدّ هذه الخرائط بمثابة أنظمة إنذار مبكر يمكن التنبؤ من خلالها على احتمال حدوث حريق ما ضمن المحمية عندما تتوفر الشروط الملائمة لذلك. This study includes a full analysis of climatic, vegetation, and topographical factors in Nabe Matta preserve (Drekish Region – Tartous Governorate – Syria), which is considered as the most important factors affecting forest fires. The data were collected for each fire and analyzed by statistical programs (SPSS) and (EXCEL), and the relationship between these multiple factors and the phenomenon of recurrence of fire in one area (fire risk region) was studied. Then the data and the results of the analysis and multi relationship had been studied within the geographic information system software (GIS) to obtain the map of fire risk region, as well as results from topographic maps (1:50.000), aerial photographs (1:25.000), and the needed maps were designed for the study such as (slope map -  aspect map -  vegetation cover map - infrastructure map - fire risk region map),then places of monitoring towers and centers of rapid intervention in high-risk areas have been proposed for the occurrence of fires. These maps are considered as warning systems and with it we can predict the probability of any fire in the Preserve when the appropriate conditions are provided for it.